2014
DOI: 10.1186/1472-6823-14-93
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis, vertebral fractures and metabolic syndrome in postmenopausal women

Abstract: BackgroundThe combined effect of the metabolic syndrome (MS) risk factors on bone health has led to controversial results and it is still not clear whether this effect is protective or detrimental. The study aimed to examine the association between MS and bone mineral density (BMD), osteoporosis, and vertebral fractures (VFs) among ambulatory older postmenopausal women.Methods270 post-menopausal women with a mean age of 61.0 years ± 7.8 (50 to 90) with no prior known diagnosis of osteoporosis were recruited. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 40 publications
5
37
0
9
Order By: Relevance
“…Because waist circumference, a main factor for the development of MetS, is highly correlated with body mass index and weight, the adjustment of body mass index or weight may over-adjust the association between MetS and bone mineral density and consequently distort the clinical significance of this association [20]. Therefore, in the analyses that did not account for body mass index, weight, and height, MetS was inversely associated with lower bone mineral density in the US populations [8] and osteoporosis in Caucasian postmenopausal women [7].…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Because waist circumference, a main factor for the development of MetS, is highly correlated with body mass index and weight, the adjustment of body mass index or weight may over-adjust the association between MetS and bone mineral density and consequently distort the clinical significance of this association [20]. Therefore, in the analyses that did not account for body mass index, weight, and height, MetS was inversely associated with lower bone mineral density in the US populations [8] and osteoporosis in Caucasian postmenopausal women [7].…”
Section: Discussionmentioning
confidence: 83%
“…Some studies have shown that MetS or its components are a detrimental factor [3][4][5]. In other studies, MetS was a beneficial factor before adjusting for weight and height or for body mass index [6][7][8][9] and was not a risk factor by gender [10]. In addition, a meta-analysis suggested a negative effect of MetS on bone mineral density in men but not in women [2].…”
Section: Introductionmentioning
confidence: 94%
“…This may perhaps also explain why patients with metabolic syndrome have lower bone mineral density (BMD) than expected after adjustment for confounders (26) and a slightly increased risk of fractures (27). Unadjusted, the higher body mass index (BMI) that occurs in metabolic syndrome is associated with higher BMD (28).…”
Section: Altered Bone Turnovermentioning
confidence: 99%
“…Treatment of postmenopausal osteoporosis is mainly hormone replacement therapy, but this therapy is often accompanied by adverse reactions, limiting its use (2,3). The pressing task is to identify a new way to treat PMO that can prevent osteoporosis without causing adverse reactions.…”
Section: Introductionmentioning
confidence: 99%